Yeast-based automated high-throughput screens to identify anti-parasitic lead compounds. Issue 2 (February 2013) - Bilsland, Elizabeth; Sparkes, Andrew; Williams, Kevin; Moss, Harry J.; de Clare, Michaela; Pir, Pınar; Rowland, Jem; Aubrey, Wayne; Pateman, Ron; Young, Mike; Carrington, Mark; King, Ross D.; et al.
Abstract : We have developed a robust, fully automated anti-parasitic drug-screening method that selects compounds specifically targeting parasite enzymes and not their host counterparts, thus allowing the early elimination of compounds with potential side effects. Our yeast system permits multiple parasite targets to be assayed in parallel owing to the strains' expression of different fluorescent proteins. A strain expressing the human target is included in the multiplexed screen to exclude compounds that do not discriminate between host and parasite enzymes. This form of assay has the advantages of using known targets and not requiring the in vitro culture of parasites. We performed automated screens for inhibitors of parasite dihydrofolate reductases, N -myristoyltransferases and phosphoglycerate kinases, finding specific inhibitors of parasite targets. We found that our 'hits' have significant structural similarities to compounds with in vitro anti-parasitic activity, validating our screens and suggesting targets for hits identified in parasite-based assays. Finally, we demonstrate a 60 per cent success rate for our hit compounds in killing or severely inhibiting the growth of Trypanosoma brucei, the causative agent of African sleeping sickness.